Reclaiming Female Agency through Écriture Féminine in Carol Ann Duffy’s The World’s Wife - Fauziah Rahmalia, Salma; Assiddiqi, Hasbi; Nurrachman, Dian (Jurnal Ragam Pengabdian, 2026)
This study examines the textual strategies used to reclaim female agency in Carol Ann Duffy’s poetry collection “The World’s Wife” through Hélène Cixous’s framework of écriture féminine. While past research heavily generalizes historical or mythological adaptations, this paper addresses a critical gap by analyzing the exact linguistic subversion and structural reconstruction of the female body and voice. Applying a mimetic approach and qualitative close reading, this study analyzes three specific poems: "Little Red Cap," "Queen Kong," and "Mrs Rip Van Winkle." The findings show that female liberation functions as a continuous, structured journey: developing from the deconstruction of internal psychological and spatial fears in "Little Red Cap," transitioning into a radical subversion of the masculine gaze through humor and desire in "Queen Kong," and culminating in complete somatic independence and autonomous creative expression in "Mrs Rip Van Winkle." Ultimately, this study demonstrates that Duffy’s revisions operate beyond simple thematic commentary; they serve as a radical practice of écriture féminine that successfully weaponizes aesthetic structures to destroy traditional patriarchal binary systems in literature.